THE FIRST CZECH-UKRAINIAN LEGAL DICTIONARY - ГАЗДОШОВА, Оксана (Comparative Legilinguistics, 2012)
The paper presents Halyna Myronova and Oxana Gazdosova´s Czech-Ukrainian Legal Dictionary (Česko-ukrajinský právnický slovník) published in 2009. There are also given problems that appeared while compiling the dictionary, the most difficult being the necessity to choose the relevant equivalent from a synonymy chain. Further, hypernymous and hyponymous relations among the legal terms had to be analyzed – paronymy and homonymy. An attention is focused on translation of words of foreign origin, internationalisms or translation of realia.